Soluble B7-H3 (sB7-H3) is over-expressed in the serum of type 1 diabetes patients. (September 2018) - Fang, Chen; Li, Sicheng; Xu, Rongqin; Guo, Heming; Jiang, Rong; Ding, Sisi; Chen, Xiaohong; Huang, Yun; Hu, Ji; Liu, Cuiping; Tu, Yifeng
Abstract: Type 1 Diabetes (T1D) is an autoimmune disease resulting from insulin-secreting β-cells mediated by autoreactive T cells. We demonstrated increased level of sB7-H3 in T1D patients than in healthy control group. This result suggests that B7-H3 may be may be a promising biomarker associated with the pathogenesis of T1D.